Subjective aging - measurement issues, developmental consequences, and malleability in midlife and early old age - Gabrian, Martina (2016)
Previous research has established subjective aging as a predictor of a broad range of developmental outcomes, including physical and mental health, cognitive functioning, and longevity. Recent developments in the field include more sophisticated multidimensional approaches to subjective aging that have been proposed as a means to gain a better understanding of the mechanisms and pathways that link subjective aging to developmental outcomes. Moreover, subjective aging researchers have insisted that the manifestations and developmental implications might change as individuals move through different life stages. Finally, given the detrimental long-term effects of a negative view on aging, subjective aging might become an important vehicle within gerontological interventions. However, an informed statement about promising intervention strategies requires more research to examine the potential for short- and long-term intraindividual change in subjective aging and to determine potential risk groups that have a particularly negative view on aging. Related to these open research questions, the four individual studies of this cumulative dissertation address a selected range of three overarching thematic areas: measurement issues, developmental consequences, and malleability of subjective aging phenomena. Research questions related to measurement issues involve the advantages and disadvantages of a domain-specific over global measurement approaches (Chapters 2 & 4); the manifestation of subjective aging phenomena in everyday life (Chapter 2); and the potentially changing meaning of subjective aging across the second half of life (Chapters 3 & 4). In terms of developmental consequences, two studies in this thesis focus on the role of subjective aging as a predictor of different health and well-being dimensions (Chapters 3 & 4). Finally, the malleability of subjective aging phenomena is investigated in terms of longitudinal change trajectories over 12 years (Chapter 4) as well as in terms of the potential short-term manipulation of subjective aging by means of experimentally induced cognitive aging experiences (Chapter 5). Overall, the thesis provides support for the notion that the salience of subjective aging domains changes across the adult life span. Future research should therefore adopt a life-span perspective on subjective aging, which asks for the mechanisms that link subjective aging to developmental outcomes during specific life phases and life contexts. Such a life-span perspective is also considered necessary for the development of tailored subjective aging interventions that take into account life-span specific needs and requirements. Middle-adulthood emerged as a critical time period for interventions, given that the average downturn in Attitude Toward Own Aging across the middle-adult years varied largely between individuals, thus pointing to some extent of plasticity of subjective aging during midlife. However, the results of the experimental study indicate that intervention strategies aiming at creating a greater awareness for age-related gains need to be developed with caution. A promising strategy might be to draw attention to the domains in which older adults themselves indicate to have various gain experiences, such as interpersonal relationships and social-cognitive and social-emotional functioning.